Gel strength and stability characterization of ultrasound treated whey protein foams - Tan, Mei Ching; Chin, Nyuk Ling; Yusof, Yus Aniza; Taip, Farah Saleena; Abdullah, Jaafar (Elsevier, 2014)
Ultrasound treated whey protein foam at 10% concentration was characterized rheologically for its gel strength and stability. The 400 W ultrasound treatment at 20, 40 and 60% amplitude for 5, 15 and 25 minutes had increased gel strength up to 31% and improved foam stability with reduced foam drainage by 31%. The continuous network of the treated whey protein foam remained as a weak gel with tan δ values > 0.1 although the overall treated sample had a slight increase of gel strength from 121 to 147 Pa·s1/z compared to the untreated at 112 Pa·s1/z.